METHODOLOGICAL FUNDAMENTALS OF THE ASSESSMENT OF THE RECREATIONAL TERRITORIES RESOURCE POTENTIAL - Nazar STUPEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The methodological approach to the comprehensive assessment of the recreational territories resource potential which implies an integral index use that takes into account the system of indicators according to the following components: nature and resource, historical and cultural, social and economic and ecological ones, has been made on the basis of the analytical generalizations and identified problems in the recreational resources study. Applying the proposed methodological approach according to type and component principle will enable to identify regions with similar natural properties, social and economic state, infrastructure support with the purpose of effective spatial planning of the recreational sphere development, as well as to determine the strategic directions of the recreational territories resource potential implementation. On the basis of the developed methodical approach, an assessment of the level of the recreational territories resource potential in Ukraine has been done. According to the calculations of the integral index, conducted in the regions of Ukraine, they have been grouped as to the following levels of the recreational territories resource potential: high, medium, low and very low. It is established that the Autonomous Republic of Crimea (final assessment 0.78) has the optimal conditions for the implementation of resource potential and the development of recreational territories among the regions of Ukraine. The potential is lower in Lviv (index – 0.61), Odesa (0.54) and Transcarpathian (0.51) regions. At the same time, most regions of Ukraine have a low level of the recreational territories resource potential compared to the best analogs in the country.